2013
DOI: 10.1037/a0028818
|View full text |Cite
|
Sign up to set email alerts
|

Predictive effects of good self-control and poor regulation on alcohol-related outcomes: Do protective behavioral strategies mediate?

Abstract: In the present study, we examined whether use of protective behavioral strategies mediated the relationship between self-control constructs and alcohol-related outcomes. According to the two-mode model of self-control, good self-control (planfulness; measured with Future Time Perspective, Problem Solving, and Self-Reinforcement) and poor regulation (impulsivity; measured with Present Time Perspective, Poor Delay of Gratification, Distractibility) are theorized to be relatively independent constructs rather tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
44
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 62 publications
3
44
1
1
Order By: Relevance
“…A recent study found that protective behavioral strategies (e.g., limiting alcohol consumption, alternating between drinking alcohol and non-alcoholic beverages, using a designated driver, etc. ; Martens, Pedersen, LaBrie, Ferrier, & Cimini, 2007) mediated the association between SC and drinking (Pearson et al, 2013). Therefore, it makes sense that general levels of self-control would protect against heavy drinking.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study found that protective behavioral strategies (e.g., limiting alcohol consumption, alternating between drinking alcohol and non-alcoholic beverages, using a designated driver, etc. ; Martens, Pedersen, LaBrie, Ferrier, & Cimini, 2007) mediated the association between SC and drinking (Pearson et al, 2013). Therefore, it makes sense that general levels of self-control would protect against heavy drinking.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has further shown that SC and the severity of alcohol-related problems are negatively associated (Dvorak, Simons, & Wray, 2011). Thus, SC has consistently been shown to negatively relate to problematic drinking (Bogg, Finn, & Monsey, 2012; Huhtanen & Raitasalo, 2012; Pearson, Kite, & Henson, 2013). Additionally, SC has been linked to reduced alcohol-related problems through greater implementation of protective behavioral strategies such as limiting alcohol consumption and using a designated driver (Pearson et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Poor selfcontrol is typically defined by an inability to focus, monitor and control one's behavior, accurately account for consequences, delay gratification, and plan (Pearson, Kite, & Henson, 2013). In contrast, positive or good self-control is defined as the ability to monitor and modify one's own behavior according to potential consequences.…”
mentioning
confidence: 99%
“…Mechanisms through which good self-control contributes to drinking outcomes are also consistent with their distinction from bottom-up personality risk. For example, Pearson and colleagues found indirect effects of good self-control on alcohol problems through its influence on manner of drinking and limiting drinking strategies (Pearson et al, 2013). These mediating variables reflect conscious efforts to regulate behavior with the former designed to reduce alcohol-related harm and the latter reflecting efforts to limit the amount consumed.…”
mentioning
confidence: 99%